PD-1 combined with lenvatinib and TACE for the transformational treatment of hepatocellular carcinoma combined with portal vein tumor thrombus: a case report and literature review - Liu, Sheng; Xiong, Rui; Duan, Chuanyi; Tang, Jiang; Yin, Tao; Dai, Sisi (Frontiers in Oncology, 2023)
Background The prognosis of hepatocellular carcinoma combined with portal vein tumor thrombus is poor, with a median survival of only 3-6 months. PD-1 combined with targeted therapy may provide an opportunity for patients with BCLC C stage hepatocellular carcinoma combined with portal vein tumor thrombus to undergo radical surgery, significantly prolonging their survival time. Case presentation A middle-aged 51-year-old male who was diagnosed with hepatocellular carcinoma combined with portal vein main stem tumor thrombus at our center in May 2020, with a BCLC stage of C, liver cirrhosis, HBV infection, and preoperative evaluation as unresectable. The liver function was Child-Pugh A. The initial treatment was lenvatinib combined with PD-1 therapy, followed by one cycle of TACE treatment. The tumor and thrombus volume significantly reduced, followed by continuous TACE combined with immunotherapy and targeted therapy, leading to the appearance of portal vein main stem emboli. After multidisciplinary discussion, surgical resection was performed, and the embolus was removed, achieving a cure. The patient has been tumor-free for over 34 months. Conclusion PD-1 combined with lenvatinib and local TACE create conditions for radical surgery, and it is hoped that more real-world research data can provide better evidence for the transformational treatment of hepatocellular carcinoma combined with portal vein tumor thrombus.